Evaluation of the Results of Glaucoma Surgery Using Optical Coherent Tomography (Literature Review) - I. I. Khusnitdinov (Oftalʹmologiâ, 2019)
Optical coherence tomography (OCT) is a noncontact method that provides two-dimensional (three-dimensional for some models) highresolution images of the anterior eye segment, with an axial resolution in the range from 3 to 20 µm. Two OCT diagnostics platforms are available: time-domain and spectral OCT. OCT provides a qualitative and quantitative assessment of the most important structures involved in the glaucoma pathogenesis: the state of the optic nerve head, the thickness of the nerve fiber layer, the anterior chamber angle and the trabecular apparatus. The OCT advantage is the ability to visualize surgically formed outflow tracts in the early postoperative period after antiglaucoma surgery. The OCT studies of the antiglaucomatous surgery zone are presented in detail in the literature, namely, the assessment of such biometric parameters of filtering bleb (FB) as wall thickness and reflectivity, radial length and height. According to the literature, the presence of a multi-layer filtration cushion 6 months after the operation indicates a favorable prognosis for the duration of the hypotensive effect of the operation. Such signs as low reflectivity of the filtration cushion wall and the presence of episcleral fluid are in most cases associated with a successful outcome of trabeculectomy. OCT studies of a filtration cushion after trabeculectomy make it much easier to choose an area for revision and nidling. In addition, OCT is used to assess anatomical features in the field of surgical intervention with drains and drainage devices. Currently OCT is widely implemented at the prehospital stage, however, engineers did not stop at the achieved level and carried out the integration of spectral OCT with an operating microscope. The possibilities of intraoperative imaging with cataract phacoemulsification (FEC) and trabeculectomy, implantation of the Ahmed valve, reconstruction of the anterior chamber angle, revision of the filtration bag and nidlinge are described in the literature. Conclusion. OCT is a very valuable method of intravital imaging of the antiglaucoma operation zone. It allows assessing the level of retention of intraocular fluid, determining the functional activity, the location of drains and drainage devices both in the early and late postoperative period.